The competitive destination : a sustainable tourism perspective / J R Brent Ritchie, Geoffrey I Crouch - Ritchie, J. R. Brent
The purpose of this book is to provide a framework for understanding the complex and multi-faceted nature of the factors that affect destination competitiveness. It provides guidance on how to create successful destinations by presenting a conceptual model of destination competitiveness.